Impact of value chain linkage on sustainable agricultural economic development in the context of industrialization and modernization in Vietnam - Nguyen, Dung Tuan (Asian Economic and Financial Review, 2025)
Agriculture is a critical area of focus, significantly contributing to the transformation of agricultural production systems toward enhancing value addition. This shift aims to address productivity challenges and meet the growing needs of the global population sustainably. Linking agricultural value chains integrates separate development stages to enhance value, boost the competitiveness of output products, and create a dynamic and efficient new production ecosystem. This study explores the effects of value chain linkage on sustainable agricultural economic development within the framework of industrialization and modernization in Vietnam. Using quantitative research methods, this study employs exploratory factor analysis (EFA) and structural equation modeling (SEM) analysis on a sample of 503 participants, including managers, workers, and farmers from business organizations and cooperatives in ecological agricultural areas. The research findings reveal significant contributions by demonstrating the direct and positive impact of value chain linkage on sustainable agricultural economic development, as well as the mediating role of outward-facing culture in the relationship between these two factors. Based on the results, the study proposes a number of recommendations for the sustainable development of the agricultural economy in Vietnam in the context of industrialization and modernization. The research results open up new and valuable directions for further research.